The European social model : modernisation or evolution? - Adnett, Nick.; Hardy, Stephen T. (Cheltenham, UK : Edward Elgar, 2005)
This book explores the development of the European Social Model and questions whether the relatively high level of social protection provided, both in terms of social welfare provision and in the creation of workers' rights and employment regulations, is sustainable
Includes bibliographical references (p. 213-231) and
index.
&#x000A
osa 24/09/14
Loans
Keywords: European Union countries -- Social policy; European Union countries -- Economic policy